Optimisation studies for wind power generation in Malaysia - Manoharan, Manoorathy (2020)
This research addresses a gap in the market for harnessing wind energy in Malaysia. While there is a global shift in the quest for renewable energy (RE) sources, non-renewable energy sources continue to dominate Malaysia’s electricity production. In recent years, Malaysia has explored alternative RE sources in its national fuel policies and has focused on biomass and solar. A cleaner source of RE-wind has been largely under-explored. Several early studies on Malaysia have exerted a cautionary note due to the low wind speeds prevalent. Moreover, most studies have relied on statistical estimations and very few studies have used wind analysis software to analyse the wind energy potential in Malaysia. There is also evidence in the literature that there is a dearth of initial wind characteristic studies and spatial wind mapping in Malaysia. This study contributes to addresses this gap using robust estimation techniques.